TOURIST DIRECTION OF CROSS-BORDER REGIONS DEVELOPMENT OF RUSSIA - Stepanova, Svetlana Victorovna; Shulepov, Vladimir Ivanovich (Journal of Applied Engineering Science, 2017)
The increasing role of the tourist scope of activity in the economy of many countries and regions of the world rationalized the proposed topic of the research. The development of tourism in the cross-border regions of Russia is regarded as a promising/priority trend for the regional development. At the turn of XX-XXI centuries in age of globalization and integration processes in the international community the socio-economic changes in Russia have brought dramatic changes in the logic of the development of Russian regions, and have formed the basis of the intensification of development and utilization of the capacity of cross-border areas, including tourist and recreational development. The purpose of the research is to describe the results of the study of qualitative changes in the development of tourism in the cross-border regions of Russia. The article represents the methodological approach to the assessment of the development of tourism and recreation activities of cross-border regions of Russia, as well as it substantiates the long-term benefits of tourism and recreation development. The study is carried out with a comparative analysis of the development of tourism indicators in Russia and thirty-seven regions, which have the land state border, for the period of 2002-2014 yrs. The holistic character of the research is contingent upon taking into account the reasonable and sufficient key indicators of tourist scope of activity: the tourism and hotel services, the dynamics of tourist mobility, and the development of tourist infrastructure. The article has theoretical and practical relevance for the scientists, researching the problems of development of tourism in the cross-border belt of Russia, for the authorities of the cross-border regions, as well as for the representatives of tourism industry.